2019
DOI: 10.1016/j.ufug.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Do small green roofs have the possibility to offer recreational and experiential benefits in a dense urban area? A case study in Helsinki, Finland

Abstract: Urban areas cover less than 3% of the earth's surface (SEDAC, 2011), but house more than half (54%) of the world's population (United Nations, 2014). Furthermore, it has been projected that 66% of the population is urban by 2050 (United Nations, 2014), which means an increase in residential and other built areas. This sets pressures for preserving and enhancing good quality natural and semi-natural urban green (and blue) environment, including, e.g. forests, parks and seasidesthe so-called green infrastructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 79 publications
2
31
0
Order By: Relevance
“…We compiled a set of statements that would measure the six perceived environmental aesthetic qualities of green and blue spaces: multisensory beauty, diversity, coherence, scale, mystery, and sublimity. We selected most of the statements (21 items) from questionnaires that we had used earlier in our studies exploring experiential qualities in urban forests (Hauru et al, 2014(Hauru et al, , 2012Koskinen, 2013), urban parks (the authors, unpublished data), and on green roofs (Mesimäki et al, 2019), and rephrased some of them to better meet this study's objectives. The rest of the statements (15 items) were generated specifically for this study, based on the literature introduced in section 1.1.…”
Section: The Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…We compiled a set of statements that would measure the six perceived environmental aesthetic qualities of green and blue spaces: multisensory beauty, diversity, coherence, scale, mystery, and sublimity. We selected most of the statements (21 items) from questionnaires that we had used earlier in our studies exploring experiential qualities in urban forests (Hauru et al, 2014(Hauru et al, , 2012Koskinen, 2013), urban parks (the authors, unpublished data), and on green roofs (Mesimäki et al, 2019), and rephrased some of them to better meet this study's objectives. The rest of the statements (15 items) were generated specifically for this study, based on the literature introduced in section 1.1.…”
Section: The Questionnairementioning
confidence: 99%
“…fast bikers), overcrowding, or noise. The inclusion of such disruptive elements might mean an improvement for PEAQS as well -however, adding negative statements is not advisable, as they may impact the factor analysis, so that the solution is related to the negative phrasing rather than the actual meaning of the statements (see Mesimäki et al 2019).…”
Section: Further Development and Applied Value Of Peaqsmentioning
confidence: 99%
“…Approaches used in these reviewed articles focus on subjective WB, using the participatory process, personal observation, experience, social survey, questionnaire, manipulated reality, or fuzzy cognitive mapping [20][21][22][23][24][25]. Others objectivize WB evaluation using literature review, field research, spatial analysis involving GIS and remote sensing, land use, landscape metrics, statistical methods [26][27][28][29][30][31], or a combination of subjective and objective WB evaluation methods [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The GR space could be optimized to mimic the memories of natural experiences, depending upon the visual or physical access demands as per the employees in the business districts. Along this line, Mesimäki et al [167] observed that GRs provide experiential and recreational benefits. The authors' findings indicated that even a small but aesthetic accessible GR has the potential to offer a moment of respite in the middle of strenuous urban life [167].…”
Section: Social Preference and Acceptancementioning
confidence: 97%
“…Along this line, Mesimäki et al [167] observed that GRs provide experiential and recreational benefits. The authors' findings indicated that even a small but aesthetic accessible GR has the potential to offer a moment of respite in the middle of strenuous urban life [167].…”
Section: Social Preference and Acceptancementioning
confidence: 97%